アスカ カンソク キョテン ノ ハイスイコウ クッサク ト コウテイ ノ ジョウショウ - 石沢, 賢二; イシザワ, ケンジ; 竹内, 貞男; タケウチ, サダオ; 高橋, 昭好; タカハシ, アキヨシ; Ishizawa, Kenji; Takeuchi, Sadao; Takahashi, Akiyoshi (1990)
P(論文) あすか観測拠点の排水孔を基地から50mの位置にスチームドリルで掘削した。排水孔は, 直径40cm, 深さ27.5mである。掘削スピードは, 4m/hで, 造水および蒸気発生に使用した灯油の総量は, 110lであった。汚水は各タンクにためられた後, 特殊なヒーターで加温されたパイプを通って排水孔に捨てられる。排水孔の底面は最初の約5カ月で7m上昇したが, 上昇速度は, それ以降減少し, 3年間で594klを捨てて, 11.6m上昇した。雪面下の排水の浸透域の広がりは, 形状を円錐体と仮定すると半径は約13.7mになる。 A borehole for sewage disposal was drilled in the snow at Asuka Station (71°31′34″S, 24°08′17″E, 930m a. s. l.) in January 1987. The borehole, 400mm in diameter and 27.5m in depth, was drilled at 50m apart from the main hut using a steam drilling system. The drilling speed was 4m/h between the surface to 20m depth. Total amount of kerosene used for melting snow and steam generation was 110l. Sewage stored in three tanks is directed to the borehole through a heated pipe. The bottom of the borehole rose about 7m in first 5 months, but after that the rising speed decreased gradually. The bottom rose 11.6m up during a period of three years when 594kl waste water was discharged. If we assume the contaminated area is cone-shaped, the cone's radius is calculated as 13.7m. departmental bulletin paper